Journal de la Fédération Graphique Internationale I.G.F.-F.G.I. = . Giornale della Federazione Grafica Internazionale
Continues: Communications de la Fédération Graphique Internationale ... (ZK 30747). - Engl. ed. : Journal of the International Graphical Federation ... (ZK 40429). - German ed. Journal der Internationalen Grafischen Föderation...(ZK 40427). - Dan. ed.: Journal från Internationella Grafiska Federationen.